Treatment of pseudo Class III malocclusion by modified Hawleys appliance with inverted labial bow - K S Negi; K R Sharma (Wolters Kluwer Medknow Publications, 2011)
Pseudo Class III malocclusion is characterized by an anterior crossbite with functional forward mandibular displacement. Various appliances have been devised for early treatment of a pseudo Class III. The aim of this article is to highlight the method of construction and use a simple removable appliance termed as "Modified Hawleys appliance with inverted labial bow" to treat psuedo class III malocclusion in the mixed dentition period. It also emphasizes the importance of differentiating between true Class III and pseudo Class III. This appliance in this type of malocclusion enabled the correction of a dental malocclusion in a few months and therapeutic stability of a mesially positioned mandible encouraging favorable skeletal growth.